Assessment of ‘Kiremt’ 2023 Climate and Climate Outlook of the Upcoming ‘Bega’ 2023/24 - Getachew, Abate; Teshome, Asaminew; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Ethiopian Meteorology Institute (EMI) generates seasonal climate outlook forums three times a year and provides this information to various socio-economic sectors. These forecasts are crucial in sustaining and developing Ethiopia, as they help minimize risks associated with weather and climate hazards while maximizing positive impacts. The institute has implemented the National Framework for Climate Services in Ethiopia (NFCS-E) and started co-designing and co-producing climate services with key socio-economic sectors. This is expected to strengthen the production, availability, delivery, and application of science-based climate predictions and services in Ethiopia.